Analisis Pencemaran Air (Studi Kasus Perairan Teluk Yos Sudarso Kota Jayapura) - Efray Wanimbo; Vera Kosntansie Mandey (Cenderawasih University, 2021)
Heavy metals are hazardous pollutants because they are toxic. If present in large quantities, it can affect the ecological and biological aspects of waters. Heavy metals are included in the group of dangerous pollutants because they have non-biodegradable properties and are easily absorbed or precipitated. This study aims to determine the concentration of heavy metals Pb, Cd, Cu, and Zn, oceanographic parameters, and pollution index in the waters of Yos Sudarso Bay. Sampling points are in three locations with consideration as pollutant-producing locations. The analysis of sea water quality was carried out descriptively by comparing the results of the analysis with sea water quality standards based on the Decree of the Minister of the Environment Number 51 of 2004 and the pollution index method to see the pollution category. The results showed that the concentration of heavy metals Pb, Cd, Cu, and Zn had exceeded the water quality standard based on the Decree of the Minister of the Environment Number 51 of 2004. For water parameters, namely the temperature had exceeded the water quality standard. standard. standard. quality standard, DO and salinity are less than quality standard, pH is below quality standard, phosphate and nitrate exceed the quality standard based on the Decree of the Minister of the Environment Number 51 of 2004. The pollution index for stations 1, 2 and 3 is lightly and moderately polluted.